Prozna avtorska dela Anje Štefan - Kristan, Marija (Revija za elementarno izobraževanje, 2010)
The prose work of Anja Štefan. Anja Štefan is an acknowledged Slovene writer, poet and collector of folk literature. She has been working in Slovenia for over ten years and has received various Slovene awards for her copyrighted works and picture books (Levstikova nagrada award, Izvirna slovenska slikanica). Her copyrighted works can be divided into poetry (Iščemo hišico, Sto ugank in Lonček na pike) and prose (Melje, melje mlinček, Lešniki, lešniki, Bobek in barčica, Štiri črne mravlje in Kotiček na koncu sveta). The majority of her poetry as well as her prose feature animals as the main character, because most of her poems and fairy tales tell animal stories. In her works we very rarely find a child as the main literary character. Anja Štefan is also a collector of folk fairy tales and fables, which she rewrites (Čez griček v gozdiček) or compiles into new editions (Zlato kralja Matjaža, Lonček, ku- haj, Čudežni mlinček, Zajec in lisica).